Overweight and obesity: a rising problem in India - Meharda, Bharat; Sharma, Sanjeev Kumar; Singhal, Govind; Kumar L., Dilip (International Journal Of Community Medicine And Public Health, 2017)
Background: Obesity is one of today’s most neglected public health problems. Childhood obesity is one of the most serious public health problems. Obesity causes cluster of non-communicable diseases and creating an enormous socioeconomic and public health burden. Methods: School based cross-sectional study was done in Udaipur city of Rajasthan. Simple random sampling method was used to obtain 1000 study subjects. Questionnaire included their general information, factor contributing to overweight and obesity. Results: 500 (50.00%) subjects were from the government schools and 500 (50.00%) from private schools. Among study participants 336 (33.60%), 332 (33.20%) and 332 (33.20%) were from 8th, 9th and 10th class respectively. 8.20% Overweight and 2.40% obesity found among school children. Overweight and obesity was found high in private schools 14.00% as compared to government schools 7.20%. The prevalence of overweight and obesity is slightly more in girls 12.60% than boys 8.60%. Conclusions: Prevalence of overweight and obesity is more than 10% in school children of Udaipur city, The prevalence of overweight and obesity was high among girls, among school children’s whose mother were working.